How to Use Iconic Image Illustration to Increase Selling Value of Fiction Works - Shienny Megawati Sutanto; Marina Wardaya (Bina Nusantara University, 2017)
This research aimed to find out how to use iconic images illustration to increase selling value of fiction works. The theoretical basis of this research was visual communication design, illustration, color, and semiotics. The method used in this research was qualitative research by doing interviews with experts who are experienced in publishing and illustration field. Another method used was observing children and fiction books which use iconic image illustration to attract consumer’s interest in order to increase books sales. The results of this study show that fiction books with iconic image illustration images have the positive response from consumers who show their interest and desire to buy them. Moreover, these results are expected to be useful for the creative industry, especially the sub-sector publishing industry when designing illustrations to be used in a book.